Potencialidad agroturística de la comunidad El Recuerdo e Isla Bonita del cantón Vinces - Sotomayor Toapanta, Yenisey (2022)
The realization of this case study is influenced by the fact that the Vinces canton has a problem that affects all the inhabitants of its community, which is the lack of promotion of agro-tourism areas such as Isla Bonita and El Recuerdo, places that fulfill a fundamental role for agricultural tourism in Vinces. Reason why this research aims to strengthen the agrotourism potential of the community to optimize the tourism development of the Vinces canton. In order to achieve the objective of the case study, research techniques such as observation have been used, which was essential to discover the problem, also necessary to understand and have a general idea of the project, another technique used was the interview, which is of vital importance to know the criteria of the community, in addition to being a support to corroborate and contrast the results obtained with the previous technique; Finally, a bibliography of books, several investigations and recent magazines was used in which the aspects and characteristics obtained through the categorization of variables were reflected. In the results obtained from the present investigation, it should be emphasized that agrotourism is an activity that has arisen in Vinces since the 18th century and brings together several inhabitants from different localities, this type of tourism generates economic income, in addition, agricultural tourism has become very popular, offering many benefits among them is the economic development of the town.